Critical Factors for Water Policy to Enable Effective Environmental Flow Implementation - Harwood, Andrew J.; Tickner, David; Richter, Brian D.; Locke, Allan; Johnson, Susan; Yu, Xuezhong (Frontiers in Environmental Science, 2018)
During the last two decades many countries have recognized the integral part that environmental flows should play in water management and have incorporated environmental flow provisions as they have updated water policy. This brief sets out generic recommendations for governments and other stakeholders on factors that, if reflected in policy frameworks, are likely to enable scaling up of environmental flow implementation. Our recommendations have been informed by a review of political, economic, social and scientific enabling factors that led to environmental flow implementation in eight rivers across the world. Legislation and regulation are pre-requisites for effective environmental flow implementation. Depending on context, we describe a number of other factors that can provide a foundation for effective environmental flows policy.